1994
DOI: 10.1289/ehp.94102s10159
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of carcinogenesis by crystalline silica in relation to oxygen radicals.

Abstract: MarylandThe carcinogenic effects of crystalline silica in rat lungs were extensively demonstrated by many experimental long-term studies, showing a marked predominance for adenocarcinomas originating from alveolar type 11 cells and associated with areas of pulmonary fibrosis (silicosis). In contrast with its effects in rats, silica did not induce alveolar type 11 hyperplasia and lung tumors in mice and hamsters, pointing to a critical role for host factors. Using these animal models, we are investigating the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…Earlier studies reported increased TGFP expression in rats with experimental silicosis Saffiotti et al, 1994). Our studies using the silicainjury model showed increased staining of TGFP ( Fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Earlier studies reported increased TGFP expression in rats with experimental silicosis Saffiotti et al, 1994). Our studies using the silicainjury model showed increased staining of TGFP ( Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Increased spontaneous production of IL-6, IL-8, and TNF-a has also been shown in silicosis and coal workers' pneumoconiosis (Vanhee et al, 1995). TGFP, was localized by immunocytochemistry in rat alveolar type I1 cells adjacent to silicotic granulomas Saffiotti et al, 1994).…”
mentioning
confidence: 99%
“…Continued silica exposure leads to an alteration in macrophage function. There is release of inflammatory cytokines, for example, IL-1, free radicals, and growth factors [3, 4]. This stimulates collagen synthesis and production of antibodies against collagen.…”
Section: Discussionmentioning
confidence: 99%
“…ROS-mediated single- and double-strand DNA breaks, DNA adduct formation, and/or transformation of bronchial epithelial cells into mesenchymal cells have been described (Lenaz, 2012). DNA damage and neoplastic transformation of the airways have been reported in the lungs of animals exposed to crystalline silica or sulfurmustard (Malaviya et al, 2010; Saffiotti et al, 1994). Lung macrophages and epithelial cells also exhibit DNA damage following exposure to ozone (Sunil et al, 2012), an effect inhibited by pretreatment with vitamin E (Cheng et al, 2003), indicating an association between oxidative stress and DNA damage.…”
Section: Pulmonary Toxicants and Oxidative Stressmentioning
confidence: 99%